2021
DOI: 10.3390/plants10030500
|View full text |Cite
|
Sign up to set email alerts
|

QTL Mapping for Gummy Stem Blight Resistance in Watermelon (Citrullus spp.)

Abstract: Watermelon (Citrulluslanatus) is an economically important fruit crop worldwide. Gummy stem blight (GSB) is one of the most damaging diseases encountered during watermelon cultivation. In the present study, we identified quantitative trait loci (QTLs) associated with GSB resistance in an F2 population derived from a cross between maternal-susceptible line ‘920533’ (C. lanatus) and the paternal-resistant line ‘PI 189225’ (C. amarus). The resistance of 178 F2 plants was assessed by two different evaluation metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…have been reported to carry sources of GSB resistance. Resistance to GSB in cucurbits has been described to be monogenic dominant, monogenic recessive and polygenic [14,15]. For example, GSB resistance in 'PI 189225' was regulated by a single gene, db [11], however, new study revealed the involvement of numerous genes with environmental variables for GSB resistance [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…have been reported to carry sources of GSB resistance. Resistance to GSB in cucurbits has been described to be monogenic dominant, monogenic recessive and polygenic [14,15]. For example, GSB resistance in 'PI 189225' was regulated by a single gene, db [11], however, new study revealed the involvement of numerous genes with environmental variables for GSB resistance [4].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies of these resistant genotypes indicated various genetical control of resistance to GSB including monogenic control in PI 189225 in previous study [11] and polygenic control with minor effects from individual genes in PI 189225, PI 482283, and PI 526233 [4,12,13]. Several studies have mapped the QTLs underlying GSB resistance in watermelon, including one QTL on chromosome 8 of PI 189225 explaining 32% of the phenotypic variations [13]; three QTLs on chromosomes 3, 5 and 7, explaining between 6.4 and 21.1% of the phenotypic variation [14] and another three QTLs on chromosomes 8 and 6 [15]. Besides, QTLs for GSB resistance have also been identi ed in other cucurbits such in Cucumber [16,17] and melon [12,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The QTL mapped by the two studies on chromosome 8 are distinct from one another. The species of Stagonosporopsis used by Lee et al (2021) is unknown. Gimode et al (2021) used a population derived from Crimson Sweet (C. lanatus) × PI 482276 (C. amarus) and S. citrulli isolate 12178A to map GSB resistance QTL on chromosomes 5 and 7 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Ren et al (2019) used a population derived from K3 (C. lanatus) × PI 189225 and an isolate of S. cucurbitacearum to map a GSB resistance QTL on chromosome 8 15 . Lee et al (2021) used a population derived from 920533 (C. lanatus) × PI 189225 and "D. bryoniae 'KACC 40937 isolate'" to map GSB resistance QTL, two on chromosome 8 and one on chromosome 6 16 . The QTL mapped by the two studies on chromosome 8 are distinct from one another.…”
Section: Introductionmentioning
confidence: 99%